Comparison between the Right and Left Distal Radial Access for Patients Undergoing Coronary Procedures: A Propensity Score Matching Analysis - Kristian Rivera; Diego Fernández-Rodríguez; Juan Casanova-Sandoval; Ignacio Barriuso; Marta Zielonka; Nuria Pueyo-Balsells; Immaculada Calaf Valls; Fernando Worner (Journal of Interventional Cardiology)
Introduction. Distal radial access for coronary procedures decreases hemostasis time, prevents radial occlusion, and improves patient comfort compared to conventional transradial access. Initially described for left distal radial access (lDRA), the right distal radial access (rDRA) is feasible. However, there are no comparative studies to date. This study aimed to evaluate the impact of the access site on vascular access and procedural performance. Methods. From August 2020 to October 2021, coronary procedures performed through distal radial access were prospectively recorded. After propensity score matching, the rDRA and lDRA were compared. The primary endpoint was the proportion of approach success. The secondary endpoints included access time, coronary procedural success, radial spasm, exposition to ionizing radiation, patient comfort, and vascular access-related complications. Results. From a total of 385 procedures in 382 patients, after a propensity score matching, 182 procedures were compared between the rDRA and lDRA. There were no differences in the baseline characteristics between the groups. Compared to the lDRA, the rDRA presented similar approach success (96.7% vs. 96.7%, p=1.0), less access time (39 (25–60) sec vs. 50 (29–90) sec, p=0.018), comparable coronary procedural success after sheath placement (100% vs. 100%, p=1.000), and not statistically significant radial spasm (2.19% vs. 6.59%, p=0.148). No differences in dose-area product (32 (20–56.2) Gy.m2 vs. 32.3 (19.4–46.3) Gy.m2; p=0.472) and fluoroscopy time (4.4 (2.5–9.1) min vs. 4.3 (2.4–7.5) min, p=0.251) were detected between the groups. No vascular access-related complications were observed in any group. Conclusions. The rDRA, compared to the lDRA, had the same proportion of approach success and procedural performance, with a slight reduction in access time for patients undergoing coronary procedures.